2014
DOI: 10.1002/chem.201403213
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Pd‐Catalyzed Allene Synthesis from Alkynes and Aryl Bromides through an Intramolecular Base‐Assisted Deprotonation (iBAD) Mechanism

Abstract: An optimized ligand-controlled palladium-catalyzed allene synthesis starting from alkynes and aryl bromides giving rise to allene products in a simple and direct manner is described. The methodology is performed in an inter- and intramolecular fashion with unprecedented scope and excellent yields. Based on mechanistic investigations and on DFT calculations, the role played by the carboxylic additive (i.e., PivOH) in controlling the selectivity of the reaction is discussed, allowing us to propose an intramolecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Possibly, the substrate leading to 3n could experience a β-H elimination upon the carbopalladation step to render an allenyl moiety, as described in other Pd-catalyzed reactions dealing with alkyl-substituted alkynes. 58 , 59 …”
Section: Results and Discussionmentioning
confidence: 99%
“…Possibly, the substrate leading to 3n could experience a β-H elimination upon the carbopalladation step to render an allenyl moiety, as described in other Pd-catalyzed reactions dealing with alkyl-substituted alkynes. 58 , 59 …”
Section: Results and Discussionmentioning
confidence: 99%
“…[16] Baudoin and co-workers found that aryl bromides could be reacted with alkynes in the presence of Pd2(dba)3 and an electron rich phosphine ligand 26 (Scheme 7a). [17] Interestingly, the addition of pivalic acid was essential to achieve high conversion to the allene products. Frantz and Neff disclosed a coupling of aryl triflates with alkynes under biphasic reaction conditions with a Pd-BobCat complexin this case the water-soluble dba ligand is extracted into the aqueous phase, preventing deleterious side reactions (Scheme 7b).…”
Section: Scheme 4 Synthesis Of Allenes From β-Halovinyl Ketones and mentioning
confidence: 99%
“…[4][5][6][7] Theoretically, the hydrogen elimination can be divided into two categories according to the hybrid state of the attached carbon atom. Hydrogen elimination from sp 3 -carbon is the most common pattern, and both alkyl and alkenyl palladium complexes [8][9][10][11] can undergo this elimination pathway, affording ole ns and allenes respectively. In contrast, the second hydrogen mode, where the eliminated hydrogen is attached to a sp 2 -carbon (also means β-elimination of vinylic hydrogen from 1 η-allylic palladium) and allene would be generated, has not been reported yet (Fig.…”
Section: Introductionmentioning
confidence: 99%